# What is the mid point of the points (-1, 2) and (3, -6)?

### 2 Answers | Add Yours

The mid point between two points ( x1, y1) and (x2, y2) is given by the point [( x1 + x2)/2 , (y1 + y2)/2]

Here we have the points (-1, 2) and ( 3, -6)

Using the expression for the mid point [( x1 + x2)/2 , (y1 + y2)/2], we get the mid point as

[( -1 + 3)/2 , (2 + -6)/2]

=> ( 2/2 , -4/2)

=> (1 , -2)

**The required mid point is (1 , -2).**

We'll apply the midpoint formula:

M = (xM ; yM)

xM = (x1 + x2)/2

yM = (y1+y2)/2

x1,x2,y1,y2 are the coordinates of the given points. Since the coordinates are added, it doesn't matter which point is the first one, whose coordinates are x1 and y1, and which point is the second one.

We'll identify x1 = -1, x2 = 3, y1 = 2 and y2 = -6

Now, we'll calculate the coordinates of the midpoint:

xM = (-1+3)/2

xM = 1

yM = (2 - 6)/2

yM = -2

**The coordinates of the midpoint M are: M(1 ; -2).**